2016
DOI: 10.1620/tjem.240.323
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Medium-Chain Triglyceride Oil Therapy in Two Japanese Citrin-Deficient Siblings: Evaluation Using Oral Glucose Tolerance Tests

Abstract: Citrin deficiency, an inherited defect of the liver-type mitochondrial aspartate/glutamate carrier isoform (citrin), may cause impairment of glycolysis because of an increase in the cytosolic NADH/NAD + ratio. We report a Japanese boy whose main complaint was recurrent hypoglycemic episodes. He was suspected as having citrin deficiency because of his peculiar preference for protein-and fat-rich food. His young sister also had a similar food preference. Both siblings were diagnosed with citrin deficiency by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The blood ketone levels might be relatively low in the hypoglycemic situation. Moreover, another study describing ketotic hypoglycemia revealed a CD case with hypoglycemic convulsion [11], while blood ketone levels (total ketone body level was 1.8 mM) were certainly elevated but relatively low for the predicted compensatory change (expected total ketone body level was > 5 mM) [8]. This result should be considered as insufficient ketosis with hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The blood ketone levels might be relatively low in the hypoglycemic situation. Moreover, another study describing ketotic hypoglycemia revealed a CD case with hypoglycemic convulsion [11], while blood ketone levels (total ketone body level was 1.8 mM) were certainly elevated but relatively low for the predicted compensatory change (expected total ketone body level was > 5 mM) [8]. This result should be considered as insufficient ketosis with hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our findings and those of previous studies, we should consider citrin deficiency when individuals experience severe hypoglycemia in childhood. 17,18 This report included nine patients with symptomatic hypoglycemia, which might indicate failed glucose homeostasis due to citrin deficiency. These attacks were recorded during a catabolic state after 1 year of life but never in infancy, except in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports have shown that patients in childhood with citrin deficiency exhibit fatigue, hypoglycemia, hyperlipidemia, growth failure, or liver dysfunction. 5,[15][16][17][18] Nutritional analysis in patients revealed that they have peculiar food preferences, such as a preference for lipidrich or protein-rich foods and an aversion to highcarbohydrate foods, which might compensate for the metabolic failure caused by citrin deficiency. 19 Okano et al reported that citrin-deficient patients had lower fatigue and quality of life scores during the adaptation and compensation stages than controls.…”
mentioning
confidence: 99%
“…Current treatment strategies for FTTDCD include diet therapy (low carbohydrate and high protein and fat) and supplements (e.g., administration of sodium pyruvate and/or MCT) (25). A case reported by Otsuka et al (26) showed MCT therapy can prevent the onset of hypoglycemia during the so-called apparently healthy period. In addition, it is speculated that long-term MCT supplementation may prevent a complication of HCC by suppressing the Wnt/Ī²-catenin pathway (27).…”
Section: Discussionmentioning
confidence: 99%